Challenges Faced by Pre-Service Teachers During Teaching Practicum - Pakpahan, Emma Martina (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Teaching English to EFL learners is a challenging task. However, most English pre-service teachers fail to meet the challenge during their teaching practicum. Therefore, it is essential for the pre-service teacher to know the challenge they may face in teaching practicum. It can help the pre-service teacher prepare themselves for teaching in a classroom. Purpose. This study aims to investigate the challenges faced by English pre-service teachers. It focused on the factor that could be a challenge that bothered the pre-service performance in their teaching practicum. The internal and external factors were also discussed. Method. Three participants participated in this research from different universities. Three of them were doing teaching practicum in the same school. Diaries and mentor feedback were used to collect the data. Results. The findings exposed that there were internal and external challenging factors in teaching. The external challenging factors were the student’s motivation and the lack of facilities. The internal ones were classroom management and teacher proficiency. Conclusion. This research contributed to the instructional practices for EFL pre-service teachers. By knowing the challenges, EFL teachers can overcome them before teaching.